Prostate carcinoma with amphicrine features: further refining the spectrum of neuroendocrine differentiation in tumours of primary prostatic origin?. Issue 6 (6th October 2017) - Prendeville, Susan; Al‐Bozom, Issam; Compérat, Eva; Sweet, Joan; Evans, Andrew J; Ben‐Gashir, Mohamed; Mete, Ozgur; van der Kwast, Theodorus H; Downes, Michelle R
Abstract : Aims: The current World Health Organization classification categorises high‐grade neuroendocrine (NE) carcinomas of the prostate into small‐cell and large‐cell types. A distinct form of carcinoma showing synchronous dual exocrine and NE differentiation, termed amphicrine carcinoma, has been described at various other sites, primarily within the gastrointestinal tract. The aim of this study was to investigate the clinicopathological features of a series of metastatic prostate carcinoma (PCa) cases with amphicrine features. Methods and results: Five cases of high‐grade PCa showing an amphicrine immunohistochemical phenotype were prospectively collected. The serum prostate‐specific antigen (PSA) level at diagnosis ranged from 38 ng/ml to 992 ng/ml (median 200 ng/ml). All five patients had metastatic disease, four at initial presentation. Microscopically, the tumours showed a solid/nested growth pattern composed of cells with amphophilic cytoplasm, vesicular nuclei, and macronucleoli. Morphological features of small‐cell or large‐cell NE carcinoma were absent. As compared with conventional high‐grade PCa, the tumour cells showed a higher level of nuclear pleomorphism, brisk mitotic activity, and a high Ki67 proliferation index (median 50%). All cases showed immunohistochemical positivity for PSA, androgen receptor, and prostate‐specific acid phosphatase, combined with diffuse or confluent/non‐focal positivity for chromogranin‐A and synaptophysin. Two hormone‐naive cases showed a clinical response to androgen deprivation therapy. Conclusion: This series highlights a previously undefined, clinically aggressive variant of PCa showing dual exocrine and NE differentiation, for which we are proposing the term PCa with amphicrine features. Increased recognition of these tumours may lead to a better understanding of their biology, and ultimately improve their clinical management.